Defining the Long-Toss: A Professional Baseball Epidemiological Study - Stone, Austin V. (Orthop J Sports Med, 2017)
BACKGROUND: Despite widespread use of long-toss throwing in baseball as a component of arm conditioning, interval throwing programs, and rehabilitation, long-toss distance and throwing mechanics remain controversial. PURPOSE: To ascertain the perceived definition of long-toss throwing through a survey of professional pitchers, pitching coaches (PCs), and certified athletic trainers (ATCs) associated with Major League Baseball. STUDY DESIGN: Descriptive epidemiology study. METHODS: Pitchers, PCs, and ATCs associated with 5 Major League Baseball organizations completed an anonymous survey that collected demographic data, personal use of long-toss throwing, and their perception of the distance and throwing mechanics that comprised long-toss. RESULTS: A total of 321 surveys were completed by 271 pitchers, 19 PCs, and 31 ATCs. For all respondents, the mean distance considered as long-toss was 175 ft (95% CI, 170-181 ft). Respondents categorized the throwing mechanics of long-toss, with 36% reporting throwing “on a line” and 70% reporting long-toss as “not on a line.” Of those throwing “on a line,” 28% reported using crow-hop footwork while 60% used crow-hop footwork when throwing “not on a line.” Interpretation of long-toss distance significantly varied by position: pitchers, 177 ft (95% CI, 171-183 ft); PCs, 177 ft (95% CI, 155-200 ft); and ATCs, 157 ft (95% CI, 144-169 ft) (P = .048). When asked when long-toss throwing is used, pitchers reported using it more frequently in preseason (P = .007), during the season (P = .015), and in the off-season (P = .002) compared with that by ATCs. Functional goals for long-toss throwing demonstrated that pitchers and PCs use long-toss for shoulder stretching more frequently than ATCs (P < .001 and P = .026, respectively). ATCs used long-toss more than pitchers for interval throwing programs (P < .001). CONCLUSION: The definition varies for long-toss throwing distance and throwing mechanics. Pitchers and PCs believe that long-toss comprised longer distances than ATCs and employed long-toss differently for strength conditioning, training, stretching, and rehabilitation. This discrepancy highlights a potential lost opportunity for protecting the shoulder. While long-toss is an important tool, a more scientific definition is warranted to better elucidate its role in enhancing throwing performance and rehabilitation.